Recent advances in management of the HIV/HCV coinfected patient. (August 2015) - Bednasz, Cindy J; Sawyer, Joshua R; Martinez, Anthony; Rose, Patrick G; Sithole, Samantha S; Hamilton, Holly R; Kaufman, Farzia S; Venuto, Charles S; Ma, Qing; Talal, Andrew; Morse, Gene D
Chronic HCV is a global epidemic, affecting approximately 150 million individuals throughout the world. The implications of HCV infection have been magnified in those who are infected with both HCV and the HIV as liver disease progression, liver failure and liver-related death are increased, particularly in those without well-controlled HIV disease. The development of direct-acting antiviral agents for HCV that allow shorter treatment periods with increased efficacy and decreased adverse events have greatly changed the outlook for HCV-infected individuals. With these advancements, growing treatment options for the coinfected population have also come. This review will address pharmacotherapy issues in the HIV/HCV coinfected population.